The Existence of the Pancasila Ideology in the Middle of a Global Ideology: Challenges for Indonesia - Awiranti, Yuniar Diah (Universitas Negeri Semarang, 2017)
Pancasila is the basis of a country that is not only wanted but is also very much needed by Indonesian citizens as a way of life in society, nation and state which includes five basic states that must uphold the values and rules contained in the Pancasila. Pancasila which is the basis of state ideology which becomes a guideline and guide in determining the signposts of goals and the nation and state of Indonesia or as a philosophical basis for the unitary state of the Republic of Indonesia which implies that the values contained in Pancasila are the basis or guidelines for state administration. Pancasila values are basically philosophical values that are fundamental so that they become a motivator in the delivery of our country as the nation's next generation in the era of globalization must hold firmly to the Pancasila as a solid foundation as the nation's personality amid the influences of international world in various aspects of life , by not doing things beyond the normal limits that will make our country divided like anarchist, racist, mocking what does not agree with us or not with us but instead we must uphold the values of social values in society and show the beauty of Indonesian citizens to the world that Indonesian citizens can maintain the unity and unity of the nation with Pancasila because this is the identity of the Indonesian people.